PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Bambang Giyarto (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine whether job satisfaction and work discipline partially or together with positive and significant to employee performance on employees, this research is a quantitative research, the sample used is 35 employees. Research data by using questionnaire method, data analysis techniques used descriptive data analysis and multiple linear regression analysis, the results showed that job satisfaction had a positif affect on the employees performance. Work discipline has a positive and significant impact on employee performance, job satisfaction and work discipline have a positive and significant impact on employee performance.